Multi-mode absorption in multi-cavity photonic crystal with two graphene monolayers. (December 2017) - Bian, Li-an; Liu, Peiguo; Li, Gaosheng; Chen, Yuwei; Liu, Hanqing; Liu, Chenxi
Abstract: Multi-mode absorption is achieved theoretically at terahertz frequencies by using the one-dimensional photonic crystal (PC) incorporating multiple Fabry-Perot resonance cavities. To simulate this multilayered structure, the method of rigorous coupled-wave analysis is adopted. Results show that for single-cavity PC with two graphene monolayers in this cavity, there are two near-unity absorption modes with low Q-factors. By cascading one empty cavity without graphene behind, an extra high-Q mode is induced in the middle. The number of modes is controlled directly by changing the positions of graphene sheets. Also, these modes are allowed to tune separately and be shifted by many manners. After another empty cavity is cascaded, two modes with higher Q-factors replace the middle one and then four near-unity absorption modes arise. Thus, the multi-cavity PC with a small number of graphene monolayers has the ability to gain multiple strong absorption modes. Highlights: Multi-mode absorption is realized by using the multi-cavity photonic crystal. Cascading empty cavities can increase the number of modes. The number of modes can be controlled by changing graphene positions. The modes can be tuned separately.